2009
DOI: 10.1097/mej.0b013e32831f47b3
|View full text |Cite
|
Sign up to set email alerts
|

Results achieved by emergency physicians in teaching basic cardiopulmonary resuscitation to secondary school students

Abstract: Emergency physicians can satisfactorily instruct secondary school students in b-CPR using PROCES, and this specific program achieves a reasonable amount of satisfactory learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 18 publications
0
29
0
3
Order By: Relevance
“…The studies showed that children and adolescents from 5 to 18 years old are able to learn certain first aid techniques. 10,11,[13][14][15][16][17][20][21][22][23][24][25][26][28][29][30][31][32][34][35][36][37]39 In addition, it was shown that children/adolescents from 11 to 18 years are willing to provide help, 12,18,19,27,33,38 and that first aid training is useful to increase their confidence or self-efficacy. 38 A strength of our project is that for the first time all the available evidence concerning the effectiveness of first aid training to children on knowledge, skills and attitudes, including evidence on their helping behaviour, is brought together into one document, which was used to develop an educational scheme based on current knowledge and practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies showed that children and adolescents from 5 to 18 years old are able to learn certain first aid techniques. 10,11,[13][14][15][16][17][20][21][22][23][24][25][26][28][29][30][31][32][34][35][36][37]39 In addition, it was shown that children/adolescents from 11 to 18 years are willing to provide help, 12,18,19,27,33,38 and that first aid training is useful to increase their confidence or self-efficacy. 38 A strength of our project is that for the first time all the available evidence concerning the effectiveness of first aid training to children on knowledge, skills and attitudes, including evidence on their helping behaviour, is brought together into one document, which was used to develop an educational scheme based on current knowledge and practice.…”
Section: Discussionmentioning
confidence: 99%
“…The PICO question can be formulated as follows: Is first aid education (related to one of the above topics) (Intervention) an effective intervention in children (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) years) (Population) to improve first aid knowledge, first aid skills and/or first aid attitudes (Outcome) compared to no first aid training (Comparison)? In addition, we searched for evidence about the helping behaviour of children.…”
Section: Selection Of Educational Pathway Contentmentioning
confidence: 99%
“…Esto hemos podido constatarlo también con el PROCES: mientras que justo tras finalizar el programa el 57% de los participantes podía considerarse, que presentaban un aprendizaje satisfactorio, este porcentaje descendía al 37% cuando se repetía el mismo test al cabo de un año de realizado el curso 36 . Cuando se comparan estos rendimientos con otros colectivos que son instruidos en RCP básica a través de cursos reglados con una mayor trayectoria, y en el caso del PROCES lo comparamos con cadetes de policía que siguieron un curso de RCP de la AHA, hemos constatado que el aprendizaje satisfactorio inicial conseguido con el PROCES fue claramente inferior (57% frente a 79% los cadetes), pero en cambio la persistencia fue superior en los estudiantes de secundaria (37% frente a 23%) 42 . Globalmente, y tras 10 años de puesta en marcha del programa, los resultados del PROCES han permitido perfilar algunos aspectos importantes.…”
Section: Resultados Alcanzados Por El Procesunclassified
“…Su afianzamiento durante los próximos años, así como su incorporación al currículo, pasan necesariamente por una apuesta clara y decidida de las administraciones públicas implicadas 42,43 . Con todo, hemos podido descubrir una serie de condicionantes, en positivo y en negativo, que pueden ser extrapolados a otros entornos semejantes, y que deben ser tenidos en cuenta en todo intento similar de introducir un programa de RCP para escolares.…”
Section: Resultados Alcanzados Por El Procesunclassified
“…In most of the studies, it has been adolescent pupils who have received a resuscitation training [24][25][26][27][28]. However, children aged 4-5 years who have received resuscitation training are also able to recognise cardiac arrest, call the emergency number and open the airways [29].…”
Section: Prerequisites For Schoolchildrenmentioning
confidence: 97%